'Are women their own enemy?' Exploration through implicit association test in the Indian public sector organisations. (9th July 2019) - Ghosh, Anindita; Dutta, Tanusree; Marathe, Gaurav Manohar
This study focuses on understanding the glass ceiling effect by exploring implicit gender bias against women at two organisational levels (senior and junior) in Indian public sector organisations. In effect, the study also attempts to understand the extent of success of governmental measures and organisational interventions in mitigating the existing gender bias. The study used implicit association test (IAT) to make classification judgments about names (male/female) and words (positive/negative). A three-way mixed ANOVA was carried out to understand the effect of gender, and work experience with response time. The findings suggest that there is implicit gender bias against women at senior levels with women showing stronger implicit bias against women at senior levels. Another finding of the study states there is no implicit gender bias against women at the entry level in the organisation indicating the partial success of pro-active governmental and organisation measures in reducing the glass ceiling effect.